PENGARUH IGNITION TIMING DENGAN BAHAN BAKAR LPG TERHADAP UNJUK KERJA MESIN BENSIN EMPAT LANGKAH SATU SILINDER - Made Mara; Made Wirawan; Towilan Ma’bud (Dinamika Teknik Mesin, 2014)
Shortage of petroleum in Indonesia is a problem that triggers people to look for alternative fuels derived fuel. One of them is the use of LPG fuel as motorcycle fuel. And to improve the performance and efficiency of the use of LPG fuel in vehicles is one of them by varying the ignition timing.The aim of this study to explore the effect of ignition timing on the torque, power and specific fuel consumption effective (SFCE) with LPG fuel using converter kit on petrol engine four stroke single cylinder Honda Astrea Prima 100 cc. In this study, the ignition timing is varied at 15˚, 17˚, 19˚ and 21˚ before TDC and to set engine rotation at 1500 rpm, 2500 rpm, 3500 rpm and 4500 rpm.The results of the experiments conducted in this study show a better performance of the engine when the ignition timing advanced earlier. Highest torque at 17˚ before TDC is 0,507 kgf.m at 4500 rpm, the highest effective power at 17˚ before TDC is 3,183 PS at 4500 rpm, and the lowest SFCE at 17˚ before TDC is 0,084 kg / jam.PS at 4500 rpm.